Attitudes toward Elderly among Nurses working in Medical-Surgical Wards in Zanjan hospitals, 2012 - Abolfazl Artishedar; Masoumeh Mortaghi ghasemi; MohammadHossein Agha Jamaat; Zeinab Ghahremani (Zanjan University of Medical Sciences and Health Services, 2015)
Background and Objectives: The population of elderly is increasing worldwide. Chronic diseases and disabilities arecommon among elderly. Attitudes of health care providers including nurses on elder people affect the quality and priorities of health and medical care. The aim of this study was to assess the attitudes of nurses working in medical-surgical wards in Zanjan hospitals toward elderly. Materials and Methods: This cross-sectional study was carried out using random sampling to recruit 110 nurses working in medical-surgical wards. Data were collected using the Kogan questionnaire and were analyzed using the T-Test and ANOVA. Results: In this study, 107 nurses (97/3%) had positive attitudes toward the elderly. The attitude scores were not significantly different in subgroups of gender, marital status, age, education, employment, work experience, job location, residency, living with an elderly, having or not having income of the elderly. Conclusion: Interventions to improve attitudes of nurses toward elderly seem to influence the quality of care provided by nurses.